Anticonvulsant activity of nicardipine in experimentally induced seizures in wistar albino rats. - M. K., Kayalvizhi (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The objective of the study was to evaluate the anticonvulsant activity of nicardipine in wistar albino rats. Methods: Anticonvulsant activity of nicardipine in a dose 10 mg/kg, and its effect with the standard drug lamotrigine (5 mg/kg) was studied in a maximal electroshock seizures (MES) experimental animal model. Results: Nicardipine in dose of 10 mg/kg showed significant anticonvulsant effect (p<0.001) and combination with standard drug lamotrigine (p<0.001) also showed more significant anticonvulsant effect in MES model. Conclusions: Nicardipine is having anticonvulsant activity and it also potentiates the anticonvulsant effect of lamotrigine in MES model.